CHARACTERISTICS OF ENDOTHELIAL DYSFUNCTION AND CARDIOVASCULAR RISK DEVELOPMENT IN CHILDREN WITH ABDOMINAL OBESITY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Abdominal obesity in children is a growing public health concern due to its association with cardiovascular diseases (CVD) and metabolic disorders. One of the key pathophysiological mechanisms linking obesity to CVD is endothelial dysfunction (ED), characterized by impaired vascular homeostasis and increased arterial stiffness. This article explores the specific features of endothelial dysfunction and cardiovascular risk formation in children with abdominal obesity, focusing on the role of inflammation, oxidative stress, and metabolic abnormalities.